When Women Say terserah The Meaning Depends on The Intonation : Women’s Prosody Analysis - Ilma, Dzikri; Syarfina, Tengku; Mahriyun; Sitinjak, Dedy Rahmad (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
The research aimed to investigate two prosodic variations (intended meaning and unintended meaning) and to deepen the understanding of the emotional nuances conveyed by women's utterances of the word terserah, contributing insights into linguistic communication and emotional expression. This research employed a descriptive qualitative analysis design. Data were collected from women of different ethnic backgrounds and ages, all married to facilitate emotional expression during recording. Three speakers participated in this research: a 31-year-old Javanese woman (P1), a 35-year-old Banjanese woman (P2), and a 40-year-old Bataknese woman (P3). Prosodic elements were measured using PRAAT, a software tool used to analyze prosodic elements such as frequency, intensity, and duration. The findings revealed significant differences between intended and unintended meanings. Intended meaning was characterized by lower pitch, lower intensity, and longer duration with a descending tone. In contrast, unintended meaning exhibited higher pitch, higher intensity, and shorter duration with an ascending tone. In conclusion, the prosodic variations indicate different emotional expressions. However, contextual factors, individual psychological conditions, body language, and facial expressions also play crucial roles in determining the emotional meaning of verbal communication. Therefore, a comprehensive understanding of emotions requires an approach that considers all these aspects together.